Development and Message Design of Course in E-Learning Based Problem Solving For Educational Mathematics - Firmansah, Muhammad Lukman Haris; Agustin, Nurul (Journal of Mathematics and Mathematics Education, 2023)
This type of learning has developed towards an online course by utilizing a variety of learning resources, media and technology.  This development is considered not to be able to facilitate the concept of learning mathematics.  A systematic and structured course design is needed so that mathematics learning can be presented in a course design by following the existing learning steps.  One of the learning steps that can be used to direct the contextual learning of mathematics is the problem based learning model.  To create a course with the type of problem solving, it is necessary to organize messages by utilizing available resources.  This course model was developed with the ADDIE development research model to produce a feasible product.  Based on the evaluation of the course display, it was found that the presentation of the course averaged 75%, the use of media and technology averaged 80%, and the utilization of learning resources averaged 80%.  From these results it is stated that course based problem solving can be used to present contextual mathematical concepts